Work Stress among Vietnamese Marketing Agency Employees Before and During the COVID-19 Pandemic - Nguyen, Linh P. (2020)
This research explores the sources and the effects of work stress on Vietnamese agency employees before and during the COVID-19 pandemic and evaluates the stress management effort made by their companies. Qualitative approach was used to analyse data that was collected through 20 semi-structured, individual interviews with Vietnamese marketing agencies employees across various positions. The main findings of the research showed that Vietnamese marketing agencies employees experience work stress frequently, which has led to serious physical and psychological problems that affected their work and personal life significantly. Major sources of stress for them before the pandemic include heavy work demands, lack of support at work, poor workplace relationships, and inadequate compensation. During the pandemic, their stress level is affected by poor communication, work & non-work conflict and financial concerns. It is found that workplace support and positive individual characteristics can buffer stress effects. The findings from this research aim to contribute to Vietnamese agencies‘ understanding of stress and influence stress management practices to mitigate the impact of stress on their business. Theoretically, this study builds the understanding of work stress in the context of contemporary Asian workplace.